2004
DOI: 10.1161/01.cir.0000138933.85923.36
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia Induces Angiogenesis, Increases Coronary Reserve, and Preserves Function of the Postinfarcted Heart

Abstract: Background-We tested the hypothesis that induction of chronic bradycardia would trigger an upregulation of key growth factors and receptors, which would then lead to angiogenesis and improve coronary reserve in the left ventricle after myocardial infarction. Methods and Results-Bradycardia was induced in rats by administering alinidine via osmotic pumps beginning 1 day after coronary artery ligation. Echocardiographic analysis was conducted before and after treatment. Morphometric analysis was used in perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
68
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 48 publications
16
68
1
Order By: Relevance
“…Previous studies have shown that drug-induced bradycardia enhances vascularity and coronary reserve, preserving the function of the surviving myocardium (10,35). This angiogenic response is dependent on VEGF (35,74). It has been documented that after myocardial infarction the VEGF is increased in the surviving myocardium (29,39,64,66) as observed in the current study.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Previous studies have shown that drug-induced bradycardia enhances vascularity and coronary reserve, preserving the function of the surviving myocardium (10,35). This angiogenic response is dependent on VEGF (35,74). It has been documented that after myocardial infarction the VEGF is increased in the surviving myocardium (29,39,64,66) as observed in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that drug-induced bradycardia enhances vascularity and coronary reserve, preserving the function of the surviving myocardium (10,35). This angiogenic response is dependent on VEGF (35,74).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Various guidelines for primary and secondary therapies are about β-receptor blockers, whose administration is one of the secondary prevention strategies employed for people with acute coronary syndrome or who have had an acute MI. β-receptor blockers reduce heart rate and improve left ventricular filling and coronary perfusion by prolonging diastolic time, reducing myocardial oxygen consumption, and elevating the threshold for ventricular fibrillation, thereby reducing the incidence of malignant arrhythmia (Lei et al, 2004). However, a multinational survey at 134 sites in 19 countries discovered that 78% of patients with acute coronary syndrome used β-receptor blockers.…”
Section: Introductionmentioning
confidence: 99%